Human Induced Pluripotent Stem Cell-Derived Microvesicles Transmit RNAs and Proteins to Recipient Mature Heart Cells Modulating Cell Fate and Behavior. (24th June 2015) - Bobis-Wozowicz, Sylwia; Kmiotek, Katarzyna; Sekula, Malgorzata; Kedracka-Krok, Sylwia; Kamycka, Elzbieta; Adamiak, Marta; Jankowska, Urszula; Madetko-Talowska, Anna; Sarna, Michal; Bik-Multanowski, Miroslaw; Kolcz, Jacek; Boruczkowski, Dariusz; et al.
Abstract: Microvesicles (MVs) are membrane-enclosed cytoplasmic fragments released by normal and activated cells that have been described as important mediators of cell-to-cell communication. Although the ability of human induced pluripotent stem cells (hiPSCs) to participate in tissue repair is being increasingly recognized, the use of hiPSC-derived MVs (hiPSC-MVs) in this regard remains unknown. Accordingly, we investigated the ability of hiPSC-MVs to transfer bioactive molecules including mRNA, microRNA (miRNA), and proteins to mature target cells such as cardiac mesenchymal stromal cells (cMSCs), and we next analyzed effects of hiPSC-MVs on fate and behavior of such target cells. The results show that hiPSC-MVs derived from integration-free hiPSCs cultured under serum-free and feeder-free conditions are rich in mRNA, miRNA, and proteins originated from parent cells; however, the levels of expression vary between donor cells and MVs. Importantly, we found that transfer of hiPSC components by hiPSC-MVs impacted on transcriptome and proteomic profiles of target cells as well as exerted proliferative and protective effects on cMSCs, and enhanced their cardiac and endothelial differentiation potential. hiPSC-MVs also transferred exogenous transcripts from genetically modified hiPSCs that opens new perspectives for future strategies to enhance MV content. We conclude that hiPSC-MVs are effective vehicles for transferring iPSC attributes to adult somatic cells, and hiPSC-MV-mediated horizontal transfer of RNAs and proteins to injured tissues may be used for therapeutic tissue repair. In this study, for the first time, we propose a new concept of use of hiPSCs as a source of safe acellular bioactive derivatives for tissue regeneration. Stem Cells   2015;33:2748–2761